Rhetorical Devices of Pronoun on Donald Trump’s Presidential Speech “Remarks by President Trump to March for Life Participants and Pro-Life Leaders” - Nuria Setiarini; Indah Winarni; Esti Junining (Universitas Brawijaya, 2019)
Pronouns are used by the politicians in order to make significant effect in their speeches. This study is designed to describe the rhetorical devices of pronoun used by Donald Trump in his presidential speech to March For Life participants and pro-life leaders and to explain how the use of pronoun reflects the intended meaning. The research design of this study is document analysis resting on the principle of phenomenology. The finding shows that pronouns I, My, You, We, Our, and Us are used (1) to create the sense of closeness, informality, no social distance relationship, and togetherness, (2) to claim and demand for shared responsibility, and (3) to show his personal quality in addressing the event. The essence of intended meaning is that to gain trust and to persuade people to accept his vision and ideas.